12 - De la résistance congolaise à la pénétration monétaire européenne (1878-1930) : une véritable guerre des monnaies - Guillaume Nkongolo Funkwa (Afrika Zamani, 2022)
In a colonized country, control over local powers by a dominant foreign power often goes through the control of currency. This article evokes such a reality based on the case of the Democratic Republic of Congo. It demonstrates how the Belgian King Leopold II between, his envoys and the following colonial government have waged war between 1878 and 1930 through prescriptions, decrees, instructions and threats meant for the control of the Congolese trade via the control of money circulation. All stratagems were allowed: the establishment of a new currency (Franc of the times of Leopold), the transitory adoption of one of the traditional currency called Mitako (merchandize-money), its de-monetization and replacement with the numeral (colonial Congolese Franc), the prohibition of the traditional barter currency, etc. The article also shows how the Congolese led their resistance, or circumvented those measures through maintaining the circulation of their traditional currencies. It was the final victory of the Belgians in this war of currencies that allowed for their final and complete grip over the Congolese economy.